2006
DOI: 10.1044/1059-0889(2006/010)
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Performance on the Hearing in Noise Test Using Directional Microphones and Digital Noise Reduction Algorithms

Abstract: A direction for further research would be to identify predictive variables that could help the audiologist determine an individual's preference a priori.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
35
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 21 publications
11
35
1
1
Order By: Relevance
“…Following the adaptive procedure described by Plomp and Mimpen (1979), we measured the SRT 50 . At the fixed SNR of +4 dB, we measured the percentage of words correctly repeated.…”
Section: Methodsmentioning
confidence: 99%
“…Following the adaptive procedure described by Plomp and Mimpen (1979), we measured the SRT 50 . At the fixed SNR of +4 dB, we measured the percentage of words correctly repeated.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, the main advantage of using the correlational method is that the entire speech spectrum, though partially degraded, is always available to the listener, and thus listeners are able to take advantage of redundant speech cues while performing the task. It should also be noted that listening in a noisy condition is not only more realistic to real-life listening environments, but is also the condition in which listeners with hearing impairment ͑Alacantara et al., 2003;Kochkin, 2005;Ricketts and Dhar, 1999;Schum, 2000͒ andhearing aid users ͑Dhar et al, 2004;Gordon-Salant and Fitzgibbons, 1997;Nordrum et al, 2006;Plyler and Fleck, 2006͒ have the most difficulty. Thus, a listener's spectral weighting strategy may provide useful information when fitting hearing aids and cochlear implants.…”
Section: Discussionmentioning
confidence: 96%
“…There may have been interactions between ENR and the other algorithms that may have influenced the results, but we can only postulate the possible effect on SRTs. Previous studies have shown a statistically non-significant effect of noise reduction whether a directional microphone was turned on or off in the same aid (Boymans & Dreschler, 2000;Ricketts & Hornsby, 2005;Nordrum et al, 2006;Yuen et al, 2006). The ADM used in the current study was designed to have a flat frequency response for all polar patterns and directions (Blamey et al, 2006), so potential interactions between changes in microphone frequency response and ENR were minimized.…”
Section: Discussionmentioning
confidence: 96%
“…Ricketts & Hornsby (2005) showed no effect of ENR on speech scores at fixed SNRs of 2 and 6dB in babble noise. Several studies have shown no significant mean effect of ENR on speech understanding whether a directional or omni-directional microphone was used (Ricketts & Hornsby, 2005;Nordrum et al, 2006;Boymans & Dreschler, 2000). The literature shows that ENR (as it was fitted) in different hearing aids generally preserved speech understanding in wideband noises and that there is potential for ENR to improve speech understanding in lowfrequency noise (Van Dijkhuizen et al, 1991;Fabry et al, 1993).…”
mentioning
confidence: 98%
See 1 more Smart Citation